Legal Awareness of Bintan Island Coastal Communities In Preventing Election Crimes: Sociological Jurisprudence - Haryanti Dewi; Adhayanto Oksep; Harmain Irfan; Intan Dian Mustika; Endri Endri; Widiyani Heni; Efritadewi Ayu; Arjuna Hendra; Nengsih Neng Suryanti; Thomas Debby Sharonly; Sihombing Lamtiur Mariana Lely; Ayuandita Nisya (BIO Web of Conferences)
This research examines the legal awareness of the coastal communities on Bintan Island regarding the prevention of election crimes, using a sociological jurisprudence approach. Coastal communities in Bintan rely heavily on marine resources and exhibit low education levels, making them susceptible to exploitation during elections through black campaigns and money politics. Utilizing empirical legal research and qualitative methods, this study investigates how socio-economic factors and local customs influence legal compliance. Data were collected through surveys and interviews with community members and leaders. Findings reveal that while there is some awareness of election crimes, skepticism about law enforcement remains prevalent, further exacerbated by poverty and inadequate legal education. To address these challenges, the study recommends implementing tailored legal outreach programs and enhancing law enforcement to strengthen electoral integrity in coastal communities. By understanding the interplay between law, society, and local customs, the research provides insights into improving legal awareness and reducing election violations in Bintan Island’s coastal areas.